产冷适应复合酶菌株Pseudomonas sp.NJ197的选育、发酵条件及酶学性质 - 张金伟; 连明珠; 曾润颖 (2006)
从南极普利兹湾深海沉积物中筛选到一株同时产多种冷适应酶的菌株NJ197,细菌学形态鉴定及16S rDNA序列分析表明,该菌株属于假单胞菌属(Pseudomonas).生长特性研究表明,该菌株属于耐冷菌,其最适生长温度为5~15℃.NJ197菌株能利用多种单一的碳、氮源产酶,最适产酶温度为20℃,最高产酶温度为30℃.粗酶液经硫酸铵盐析、DEAE cellulose-52柱层析初步分离纯化后进行酶学性质的研究.该菌株所分泌复合酶中脂肪酶和淀粉酶的活力最高,它们的最适作用温度分别为30℃和35℃,最适pH值分别为9.0和9.5,对热敏感,是典型的碱性冷适应复合酶.Ca2+、Mn2+、Cu2+、Co2+、Fe3+对该复合酶有较为明显的激活作用,而Zn2+、Hg2+、Rb2+、Cd2+、EDTA则能抑制酶活.其中脂肪酶能在高浓度的SDS、CHAPS等变性剂中表现出较好的稳定性.图5表2参21 A strain NJ197, producing cold-adapted complex enzyme, was isolated fromdeep sea sediment of the Prydz Bay, Antarctic. The morphological identification and 16S rDNA sequence analysis showed that it belonged to genus Pseudomonas. The optimal growth temperature of the Pseudomonas sp. NJ197 was 5~15 ℃, indicating that it was a psychro- tolerant bacterium. The strain could use various single carbonaceous and nitrogenous substances to produce complex enzyme. Its optimal and highest temperatures for enzyme production were 20 ℃ and 30 ℃, respectively. The enzyme purification was performed by ammonium sulfate fractionation and anion exchange chromatography with DEAE cellulose-52. The activities of lipase and amylase were the strongest among the complex enzymes produced by Pseudomonas sp. NJ197, and the both were sensitive to high temperature. The optimal temperature and pH value for the lipase activity were 30 ℃ and 9.0, while those for the amylase activity were 35 ℃ and 9.5, respectively. The results indicated that they were typical alkaline cold-adapted enzymes, whose activities were stimulated by Ca~ 2+ , Mn~ 2+ , Cu~ 2+ , Co~ 2+ and Fe~ 3+ , and inhibited by Zn~ 2+ , Hg~ 2+ , Rb~ 2+ , Cd~ 2+ and EDTA. The cold-adapted lipase showed better resistance to inactivation of 1 detergents, such as SDS and CHAPS. Fig 5 , Tab 2, Ref 21 国家自然科学青年基金(No.40406029)资助~